Formação continuada de professores : uma repercussão na prática pedagógica? - Cardoso, Edilza Maria de Souza (2008)
This paper discusses the continuing formation of teachers and its effect on their performance. It also aims at analyzing if the structured knowledge being framed as a theoretical reflection has been incorporated to the teacher s practice. The focus of this study was centered on teachers who took the II Curso de Extensão Universitária em Educação de Jovens e Adultos (Second Course of College Extension in Adolescent and Adult Education) held in 2004 by Programa de Educação de Jovens e Adultos da Secretaria Municipal de Educação (Program of Adolescent and Adult Education of the City Department of Education) in the city of Rio de Janeiro together with Universidade Federal Fluminense. In order to analyze this study, twenty-one subjects were interviewed such as teachers who participated in the above mentioned course and also its active teachers together with the coordinators who were all chosen at random. A document analysis was also performed including the pedagogical proposal and the content of the course, the laws ruling teachers formation, among others. In order to answer the questions raised by this study, we have selected Antonio Gramsci, Paulo Freire, Antonio Nóvoa and Célia Linhares as the main theoretical references. When discussing teachers formation we have first outlined the political context in which the public policies that describe them are inserted. We have covered a bibliographical review on teachers continuing formation, establishing a parallel with the development of the teacher s career and highlighting the teachers political and reflexive role in the development of their job. The data collected during the research was then organized like this: the pedagogical proposal of the course, the cooperation process between the university and the city, the teachers perception of the formative process and the relationship between continuing formation and teachers practice. We have chosen to use the qualitative research so that the teachers answers would give way to a reflexive attitude about their practice.